Statics Learning from Engineering Examples - Emri, Igor.; Voloshin, Arkady; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
This textbook introduces and explains the basic concepts on which statics is based utilizing real engineering examples. The authors emphasize the learning process by showing a real problem, analyzing it, simplifying it, and developing a way to solve it. This feature teaches students intuitive thinking in solving real engineering problems using the fundamentals of Newton's laws. This book also: · Stresses representation of physical reality in ways that allow students to solve problems and obtain meaningful results · Emphasizes identification of important features of the structure that should be included in a model and which features may be omitted · Facilitates students' understanding and mastery of the "flow of thinking" practiced by professional engineers.
The Laws of Nature -- Forms of Loads and Supports -- Resultant and Equilibrium of Forces Acting at a Point -- Equilibrium of Rigid Body -- Centroids -- From the Rigid Body to Structures -- Trusses -- Beams -- Ropes -- Mixed Structures -- Friction.
Keywords: Mechanics, Applied; Solids; Solid Mechanics